Designing Institutional Models For Renewable Energy Project Sustainability - Setiartiti, Lilies; Al-Hasibi, Rahmat Adiprasetya (International Journal of Energy Economics and Policy, 2021)
Access to adequate, affordable, and reliable energy is one of the first steps to poverty alleviation, especially in the remote areas, to increase productivity, employment, and social welfare of a community. For Yogyakarta, which have no an energy source, developing renewable energy project is a strategic step to make it happen. Many projects have been carried out both to increase the amounts of renewables in the energy mix as well as to electrify remote rural areas. Unfortunately, many of these projects have failed to meet the intended target. Some renewable energy projects experienced low efficiency rates, while other renewable energy systems completely broke down without perspective on repair within only a few years of operation. This study aims to identify the sectors core problems and evaluate various renewable energy projects in order to investigate why some projects prosper, while others fail to have the right effect. Furthermore, a proper institutional model to keep sustainable renewable energy projects will be conducted to increase the productivity of rural businesses. Data obtained by using in-depth observation and Focus Group Discussion to provide answers of the problems faced to explain the phenomenon. SWOT technique used to determine supporting and hindering factors, to formulate the development strategy in achieving the proper of renewable energy project institutional model. Overall, tis research provides some important insights for local government to develop a sustainable renewable energy project. Keywords: Institutional Model, Renewable Energy Project, FGD, SWOT JEL Classifications: Q2, Q3, Q4, Q5. DOI: https://doi.org/10.32479/ijeep.11391